Infecção experimentao por cepa atípica de Toxoplasma gondii leva ao comprometimento de macrógfagos residentes e induz alterações comportamentais em modelo murino - Ramayana Morais de Medeiros Brito (2022)
The protozoan Toxoplasma gondii exhibit a great diverse population structure, with high distribution of atypical strains in South America, mainly in Brazil. The establishment of the immune response, with the production of IFN-γ, is detrimental to control T. gondii infection and to maintain the chronic stage. In this context, the work presented here sought to investigate the impact of T. gondii atypical strain infection over the immune response and immune cell, and how the cerebral infection contributes to possible behavioral alterations in experimental murine model. Firstly, BALB/c male mice were infected with ten tissue cysts of clonal ME49 or atypical TgCkBrRN2 (CK2) T. gondii strains, per gavage. Mice were submitted to behavior analysis, to determine possible behavioral changes induced by infection; afterwards, bronchoalveolar and brain populations of immune cells and the level of local inflammation and neurotrophic factors were determined by ELISA and CBA. The results showed that during chronic brain infection, it was found a dramatic decrease in the microglia population, followed by intense inflammatory infiltrate and high levels of inflammatory cytokines; besides the neuroinflammation observed, the infection caused by the atypical strain also contributed to changes in the nerve growth factor and fractalkine levels in different areas of the brain. In addition, it was also observed that chronic infection by T. gondii atypical strain induced anxiety- and depression-like behaviors. After analysing the cell population obtained in the bronchoalveolar lavage fluid, it was found that T. gondii infected mice displayed marked depletion of alveolar macrphages by apoptosis during acute stage of infection; this depletion was followed by replacement of alveolar macrophages by inflammatory monocytes that infiltrated from the periphery. Based on the results presents here, it is clear the ability of T. gondii to interfere in the resident macrophages population integrity, which can be observed in different host tissues; as well as stimulate a sustained cerebral inflammation that is related to the establishment of behavioral alterations.